Relationships between mathematics anxiety, confidence to teach mathematics, and attitudes towards mathematics in pre-service teachers - Cooke, Audrey; Hurst, Chris (Gruppo Ricerca Insegnamento delle Matematiche (GRIM), 2013)
Mathematics anxiety has been found to relate to teacher behaviours in the classroom (Choppin, 2011) and their planning for teaching mathematics (Isiksal, Curran, Koc, & Askum, 2009). In addition, Bursal and Paznokas (2006) found connections between higher confidence to teach mathematics and lower maths anxiety. The aim of this paper is to investigate the relationships between mathematics anxiety, confidence to teach mathematics, and attitudes towards mathematics.